Lunarni les - mit ali resničnost - Torelli, Niko (Zbornik gozdarstva in lesarstva, 2005)
Science has not been able to confirm the salient characteristics of moontimber, i.e. timber felled at "proper time", as "dictated" by moon phases,zodiac signs and (surprising) fixed dates. Moontimber is said to have some special and unusual characteristics: it does not rot, it is not attacked by insects, it does not burn, it is drier, it does not shrink, it does not crack, it does not bend, and it is very hard. In the present article, the Forestry Moon Calendar for the Year 2005 is presented. Most problematic apart from doubts about the impact of the lunar "impulses" on timber quality seem, for entirely calendar reasons, the "fixed" dates (e.g. March 1st) and the roleof (shifted) zodiac signs. Moontimber may indeed be of better quality, although not due to cosmic influences but owing to a wise selection of the best trees (e.g. "resonant" older spruce-wood) and careful handling after being felled.
Keywords: lastnosti; les; sečnja